Change management strategies and employees productivity: A case of selected departments in the county government of Meru, Kenya - Karimi,Grace Gitonga (Meru: Grace Karimi Gitonga, 2019)
Government around the world devolve or decentralize power with the sole aim of bringing services closer to their citizens. However, the realization of quality services by citizens is hampered by employee productivity which is in turn affected by a multiplicity of work environment factors in these devolved units of governance. A major factor that affects employee productivity is change management strategies created in these devolved or decentralized governance units.This is mainly in terms of how change management is infused and or whether the is an official reliable structure to address them.This research study specifically investigated change management strategies and employee productivity with specific reference to the county government of Meru. Particularly it sought to establish the effect of: alternative work discipline interventions, organizational culture and provision of incentives. The investigation was based on two theories, Mc Kinsey 7's model and Reinforcement and Behavior Modification theory. The study was guided by descriptive survey research design. Target population comprised of 490 staff from the department of revenue, water and irrigation and health services.The sample size comprised of 216 staff from selected Departments of county government of Meru chosen to participate in research. Stratified and simple random sampling techniques were used to select the final sampled subjects.Questionnaires were used to collect primary data in the study locale.Collected data was analyzed quantitatively using measures of central tenancy and variability; means and standard deviation. To establish the cause and effect relationship between the study variables a multiple regression model was adopted. Data was analyzed using Statistical Package for Social Scientists (SPSS) version 22.0 enabling the study to carry out inferential statistics that made possible to make decisions on the studies hypotheses. Analyzed data was presented in frequency, percentage tables. The response rate of the study was 82.41%. The study established a positive and significant relationship between the alternative work disciplines interventions,organizational culture, provision of incentives and employee productivity. Thus all the null hypotheses in the study were rejected.The study concluded that change management strategies are vital for employee productivity in the organization. The study recommendations that alternative work disciplines interventions, organizational culture and provision of incentives should be incorporated in the public sector for smooth change management strategies transition hence ensuring continued improvement of employees productivity.
Includes Appendix and Reference